Relationship between Pain Catastrophizing and Perceived Wellness among Chronic Pain Patients - Adnan N. Balisi; Celo I. Magallanes (Philippine Social Science Journal, 2023)
One of the problems being addressed in the care of chronic pain patients is pain catastrophizing, an exaggeration of the threat of pain that results in a distorted perception of patients’ quality of life. Literature has yet to explore the relationship between pain catastrophizing and the perceived wellness of chronic pain patients. This descriptive-correlational study explores the relationship between the pain catastrophizing of chronic pain patients and their degree of perceived wellness. Historical patient charts in a local physical therapy clinic were used to gather data. Male patients are significantly more likely to be non-catastrophizers. Clinically significant pain catastrophizing scores strongly correlated to lower perceived wellness [rs(33)= -0.626, p=0.000], while non-catastrophizing scores only moderately correlated to higher perceived wellness [rs(54)= -0.520, p=0.000]. Both correlations were statistically significant. The concomitance between psychosocial perceptions and chronic pain necessitates the creation of a pain counseling program by pain specialists and counselors to holistically understand and treat chronic pain patients.